MENGELOLA DIVERSITAS: PENYEBAB KEGAGALAN DAN MODEL YANG EFEKTIF - C. Marliana Junaedi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2003)
Currently, diversity grows rapidly in business and organizations that it becomes the major problem to academics and practitioners. Many organizations had attempted to implement diversity management, but they failed afterward. This article discusses the definition of diversity management, the causes of failure in implementing diversity management, and an effective model of diversity management.Keywords: diversity, diversity management, organization